A genome‐wide association study identifies novel players in Na and Fe homeostasis in Arabidopsis thaliana under alkaline‐salinity stress. (17th December 2022) - Almira Casellas, Maria Jose; Pérez‐Martín, Laura; Busoms, Silvia; Boesten, René; Llugany, Mercè; Aarts, Mark G. M.; Poschenrieder, Charlotte
SUMMARY: In nature, multiple stress factors occur simultaneously. The screening of natural diversity panels and subsequent Genome‐Wide Association Studies (GWAS) is a powerful approach to identify genetic components of various stress responses. Here, the nutritional status variation of a set of 270 natural accessions of Arabidopsis thaliana grown on a natural saline‐carbonated soil is evaluated. We report significant natural variation on leaf Na (LNa) and Fe (LFe) concentrations in the studied accessions. Allelic variation in the NINJA and YUC8 genes is associated with LNa diversity, and variation in the ALA3 is associated with LFe diversity. The allelic variation detected in these three genes leads to changes in their mRNA expression and correlates with plant differential growth performance when plants are exposed to alkaline salinity treatment under hydroponic conditions. We propose that YUC8 and NINJA expression patters regulate auxin and jasmonic signaling pathways affecting plant tolerance to alkaline salinity. Finally, we describe an impairment in growth and leaf Fe acquisition associated with differences in root expression of ALA3, encoding a phospholipid translocase active in plasma membrane and the trans Golgi network which directly interacts with proteins essential for the trafficking of PIN auxin transporters, reinforcing the role of phytohormonal processes in regulating ion homeostasis under alkaline salinity. Significance Statement: Soil salinization is a major constraint affecting crop growth and productivity, especially in arid and semi‐arid regions. Salinity and alkalinity frequently coexist in nature, being more destructive to plants than neutral salts. The exploration of genetic diversity and a comprehensive understanding of the molecular tolerance mechanisms involved in salinity‐alkalinity tolerance are essential for breeding resilient crops and thus facing one of the biggest agricultural challenges posed by climate change and increasing population.